The Accuracy of Prostate Cancer Localization Diagnosed on Transrectal Ultrasound-Guided Biopsy Compared to 3-Dimensional Transperineal Approach. (29th December 2013) - Krughoff, Kevin; Eid, Khadijah; Phillips, Jason; Stoimenova, Diliana; Smith, Daniel; O'Donnell, Colin; Crawford, E. David; Barqawi, Al
Abstract : Background . Prostate cancer is often understaged following 12-core transrectal ultrasound- (TRUS-) guided biopsies. Our goal is to understand where cancers are typically missed by this method. Methods . Transperineal 3-dimensional mapping biopsy (3DMB) provides a more accurate depiction of disease status than transrectal ultrasound- (TRUS-) guided biopsy. We compared 3DMB findings in men with prior TRUS-guided biopsies to determine grade and location of missed cancer. Results were evaluated for 161 men with low-risk organ confined prostate cancer. Results . The number of cancer-positive biopsy zones per patient with TRUS was 1.38 ± 1.21 compared to 3.33 ± 4.06 with 3DMB, with most newly discovered cancers originating from the middle lobe and apex. Approximately half of all newly discovered cancerous zones resulted from anterior 3DMB sampling. Gleason upgrade was recognized in 56 patients using 3DMB. When both biopsy methods found positive cores in a given zone, Gleason upgrades occurred most frequently in the middle left and right zones. TRUS cancer-positive zones not confirmed by 3DMB were most often the basal zones. Conclusion . Most cancer upgrades and cancers missed from TRUS biopsy originated in the middle left zone of the prostate, specifically in anterior regions. Anterior sampling may lead to more accurate diagnosis and appropriate followup.